2011
DOI: 10.1371/journal.pone.0024292
|View full text |Cite
|
Sign up to set email alerts
|

PTPN22 1858C>T Polymorphism Distribution in Europe and Association with Rheumatoid Arthritis: Case-Control Study and Meta-Analysis

Abstract: ObjectiveThe PTPN22 rs2476601 polymorphism is associated with rheumatoid arthritis (RA); nonetheless, the association is weaker or absent in some southern European populations. The aim of the study was to evaluate the association between the PTPN22 rs2476601 polymorphism and RA in Italian subjects and to compare our results with those of other European countries, carrying out a meta-analysis of European data.MethodsA total of 396 RA cases and 477 controls, all of Italic ancestry, were genotyped for PTPN22 rs24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 41 publications
4
30
0
1
Order By: Relevance
“…We report in the present study association of PTPN22 1858C→T polymorphism with susceptibility to RA among Egyptian patients, which is consistent with previous studies done on different ethnic populations such as on Iranian population [20], Italian [21] and Mexican population [22].…”
Section: Discussionsupporting
confidence: 93%
“…We report in the present study association of PTPN22 1858C→T polymorphism with susceptibility to RA among Egyptian patients, which is consistent with previous studies done on different ethnic populations such as on Iranian population [20], Italian [21] and Mexican population [22].…”
Section: Discussionsupporting
confidence: 93%
“…The PTPN22 R620W autoimmunedisease risk allele was also detected in only 1 case (3.4%), consistent with the expected frequency of this allele for the same healthy population (3.7%). 31 Another less frequent PTPN22 variant (R263Q), which has been associated with reduced risk for autoimmune disease, was observed in another patient. 32 Overall, the sequencing analysis revealed that PTPN22 and SHP-1 are not frequently mutated in CLL and that the PTPN22 autoimmunedisease risk variant is not more prevalent in CLL patients than in the general population.…”
mentioning
confidence: 92%
“…Likewise, loss of tolerance to self-antigens, which leads to stimulation of lymphocytes and other immune cells, release of cytokines, activation of complement and the production of autoantibodies, contributes to the pathogenesis of the RA [5]. Genetic factors are thought to be responsible for up 50-60% of the predisposition to RA [6]. The +1858C/T (rs2476601) single-nucleotide polymorphism (SNP) in the protein tyrosine phosphatase non-receptor type 22 (PTPN22) gene has been associated with susceptibility to multiple autoimmune diseases [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors are thought to be responsible for up 50-60% of the predisposition to RA [6]. The +1858C/T (rs2476601) single-nucleotide polymorphism (SNP) in the protein tyrosine phosphatase non-receptor type 22 (PTPN22) gene has been associated with susceptibility to multiple autoimmune diseases [3,6]. The human PTPN22 gene, is located on chromosome 1p13, and encodes a lymphoid protein tyrosine phosphatase (LYP), which is important in negative control of T cell activation and in T cell development.…”
Section: Introductionmentioning
confidence: 99%